Reliability and validity of the French version of the global physical activity questionnaire - Fabien Rivière; Fatima Zahra Widad; Elodie Speyer; Marie-Line Erpelding; Hélène Escalon; Anne Vuillemin (Elsevier, 2018)
Background: The Global Physical Activity Questionnaire (GPAQ) has been used to measure physical activity (PA) and sedentary time in France, but no study has assessed its psychometric properties. This study aimed to compare the reliability as well as criterion and concurrent validity of the French version of the GPAQ with the French International Physical Activity Questionnaire long form (IPAQ-LF) and use of an accelerometer in a general adult population. Methods: We included 92 participants (students or staff) from the Medicine Campus at the University of Lorraine, Nancy (north-eastern France). The French GPAQ was completed twice, 7 days apart, to study test-retest reliability. The IPAQ-LF was used to assess concurrent validity of the GPAQ, and participants wore an accelerometer (ActiGraph GT3X+) for 7 days to study criterion validity. Reliability as well as concurrent and criterion validity of the GPAQ were tested by the intraclass correlation coefficient (ICC), Spearman correlation coefficient for quantitative variables, and Kappa and Phi coefficients for qualitative variables. Both concurrent and criterion validity of GPAQ were assessed by Bland-Altman plots. Results: The GPAQ showed poor to good reliability (ICC = 0.37-0.94; Kappa = 0.50-0.62) and concurrent validity (Spearman r = 0.41-0.86), but only poor criterion validity (Spearman r = −0.22-0.42). Limits of agreement for the GPAQ and accelerometer were wide, with differences between 286.5 min/week and 601.3 min/week. Conclusion: The French version of the GPAQ provides limited but acceptable reliability and validity for the measurement of PA and sedentary time. It may be used for assessing PA and sedentary time in a French adult population. Keywords: Measurement, Physical activity, Psychometric analysis, Questionnaire, Reliability, Self-report, Sitting time, Validity